Vectors of Dermatobia hominis eggs in the highlands of Santa Catarina, Brazil - Paloschi, Claudio Granzotto; Ramos, César Itaqui; de Souza, Antônio Pereira; Bellato, Valdomiro; Sartor, Amélia Aparecida; Dal'Agnol, Celso Augustinho (Pesquisa Agropecuaria Brasileira, 1991)
An experiment was carried out from January 1984 to December 1987 in the highlands of the state of Santa Catarina, Brazil, to identify vectors of Dermatobia hominis eggs. Cage traps with steers as bait were located in: a) open pastures; b) areas between open pastures and woodland; and c) inside woodland. Insects from the traps were collected twice a day: a) at 18:00h to collect insects captured at day time; and b) at 07:00h, to collect insects captured during the night. The species, with the respective number of specimens and season of higher incidence, were: Fannia heydenii, 34, Summer and Autumn; Musca domestica, 19, Spring and Summer; and Morellia humeralis, 1, Summer. The highest number of specimens of vectors was observed in the trap located inside woodland. The number of vectors captured during day time was significantly higher (P < 0.05) than the number captured at night.